(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
This research was conducted to study the effect of (water with hexane) extract of Inula viscosa L. plant naturally growing on the edges of fields in Kadmous region against the bacteria Pseudomonas savastanoi pv. savastanoi, which causes olive knot disease, isolated from galls on infected Olive trees, which was grown on medium, Nutrient agar (NA), The inhibitory effect of the extract was tested by measuring the inhibition distance around the paper disc treated with the extract. Our results showed that the Taion plant extract (Inula viscosa L.) showed in its different concentrations (1,5,10,20,25) an inhibitory effect on the growth of bacteria in vitro. The inhibition percentage was 18.1% at concentration of 1%, while at the concentration of 5% was the inhibition percentage 21.8%, while the bacterial growth was inhibited 23.3% at concentration of 10%, the inhibition percentage was 27.7% at concentration of 15%. While the inhibition percentage was 33.3% at concentration of 20%, while the concentration of 25% gave 39% inhibition percentage. The results of this research showed that the Taion plant extract (Inula viscosa L.) playes an important role in control of the bacteria that cause olive knot disease in future.